2007
DOI: 10.1016/j.neurobiolaging.2006.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Age-related changes in brain activation during a delayed item recognition task

Abstract: To test competing models of age-related changes in brain functioning (capacity limitation, neural efficiency, compensatory reorganization, and dedifferentiation), young (n=40; mean age=25.1 years) and elderly (n=18; mean age=74.4 years) subjects performed a delayed item recognition task for visually presented letters with three set sizes (1, 3, or 6 letters) while being scanned with BOLD fMRI. Spatial patterns of brain activity corresponding to either the slope or y-intercept of fMRI signal with respect to set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
177
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 163 publications
(200 citation statements)
references
References 104 publications
20
177
2
Order By: Relevance
“…However, this additional right PFC activity during encoding cannot compensate for a reduction in encoding effectiveness of the left PFC, and so does not provide a benefit for subsequent memory of the encoded items. This is similar to the idea that over-recruitment might help cognition in a general way, but may not be related to performance on a specific task 42 . Regardless, the papers cited in this section indicate that one should be careful about interpreting age increases in brain activity as compensatory without sufficient evidence from behavior to support such an interpretation.…”
Section: Compensation In the Older Brainsupporting
confidence: 70%
See 2 more Smart Citations
“…However, this additional right PFC activity during encoding cannot compensate for a reduction in encoding effectiveness of the left PFC, and so does not provide a benefit for subsequent memory of the encoded items. This is similar to the idea that over-recruitment might help cognition in a general way, but may not be related to performance on a specific task 42 . Regardless, the papers cited in this section indicate that one should be careful about interpreting age increases in brain activity as compensatory without sufficient evidence from behavior to support such an interpretation.…”
Section: Compensation In the Older Brainsupporting
confidence: 70%
“…Several researchers have suggested that compensatory mechanisms might still play a role even if performance in older adults is impaired 42 . For example, increased activity in an older adult might not be associated with preserved performance on a given task to the level seen in a young adult, but this performance might be even worse without the over-recruitment.…”
Section: Compensation In the Older Brainmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have described how brain activity increases with task difficulty or cognitive load in aging (Rypma et al 2007;Zarahn et al 2007;Morcom et al 2007). Palva et al (2010) found that an increase in working memory load resulted in a strengthened brain synchrony.…”
Section: Task Loadmentioning
confidence: 99%
“…All 4 measures were then tested in a mixed model ANCOVA (Proc Mixed, SAS, Cary, NC) with diagnosis, smoking status, and diagnosis-by-smokingstatus as fixed effects and "runs" modeled as a random effect. Age was included as a covariate in all models because of the documented influence of this variable in prior studies (Fischer et al, 2005;Hesselman et al, 2001;Kwee and Nakada, 2003;Lamar et al, 2004;Ross et al, 1997;Zarahn et al, 2006). The analysis included separate within-cell variance estimates for each of the four cells.…”
Section: Discussionmentioning
confidence: 99%